The effects of Adolescent Idiopathic Scoliosis on Young People A Critical Review - Elliot, Aimee Rebecca (2013)
Introduction-This dissertation will explore the effect of Adolescent Idiopathic Scoliosis (AIS) on young people. It aims to examine the physiological, psychological and social effects of AIS, which will ultimately work towards determining the overall impact of the condition on young people.